Faktor-Faktor Yang Mempengaruhi Penegakkan Hukum Dalam Penerapan Keadilan Restoratif (Restorative Justice) Di Kejaksaan Negeri Pangkalpinang Tahun 2020-2023 - Herlina Evangelista Silalahi, Hizkia; Armanda Agustian, Rio; Toni (BULLET : Jurnal Multidisiplin Ilmu, 2024)
Restorative justice is a process where the parties involved in a particular violation meet to resolve the issue together on how to resolve the consequences of the violation for the sake of the future. The purpose of this study was to determine law enforcement in the application of Restorative Justice at the Pangkalpinang District Attorney's Office and to determine the inhibiting factors in the application of Restorative Justice at the Pangkalpinang District Attorney's Office. The method used in this study is empirical juridical with a case and law approach. The results of this study are that the Pangkalpinang District Attorney's Office in handling Restorative Justice cases has been in accordance with the concept of law enforcement itself, where in resolving the case the Public Prosecutor provides mediation which is carried out transparently and safely so that the victim feels heard and the perpetrator can admit his mistake without any coercion from any party. However, there are supporting factors and inhibiting factors in the application of Restorative Justice. Supporting factors such as the provision of a special room to handle restorative justice cases and the existence of a Restorative Justice hall and the inhibiting factors are on the part of the victim himself who does not want to reconcile.